2018
DOI: 10.1021/jacs.7b11981
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Hydrogenation with Supported Organoplatinum(IV) Catalyst on Zn(II)-Modified Silica

Abstract: Well-defined organoplatinum(IV) sites were grafted on a Zn(II)-modified SiO support via surface organometallic chemistry in toluene at room temperature. Solid-state spectroscopies including XAS, DRIFTS, DRUV-vis, and solid-state (SS) NMR enhanced by dynamic nuclear polarization (DNP), as well as TPR-H and TEM techniques revealed highly dispersed (methylcyclopentadienyl)methylplatinum(IV) sites on the surface ((MeCp)PtMe/Zn/SiO, 1). In addition, computational modeling suggests that the surface reaction of (MeCp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 118 publications
4
55
0
Order By: Relevance
“…[59][60][61][62][63][64]76 Recently, we have used 1 H{ 17 O} dipolar recoupling experiments to characterize the Brønsted acidity of surfaces. 36,65 These experiments, however, were found to have insufficient resolution to separate the O-H distances of the sites responsible for the Brønsted acidity of silica-aluminas from those of the non-acidic silanols and aluminols. One promising approach to improving the resolution is to spread the resonances along a third dimension during which the 1 H chemical shifts are allowed to evolve.…”
Section: O Identification Of Acid Sitesmentioning
confidence: 99%
“…[59][60][61][62][63][64]76 Recently, we have used 1 H{ 17 O} dipolar recoupling experiments to characterize the Brønsted acidity of surfaces. 36,65 These experiments, however, were found to have insufficient resolution to separate the O-H distances of the sites responsible for the Brønsted acidity of silica-aluminas from those of the non-acidic silanols and aluminols. One promising approach to improving the resolution is to spread the resonances along a third dimension during which the 1 H chemical shifts are allowed to evolve.…”
Section: O Identification Of Acid Sitesmentioning
confidence: 99%
“…This strategy has only been explored in very rare instances [13][14][15][16][17][18] and is different from sequential co-grafting or co-impregnation methods in which both metal sites are orthogonally attached to the support, independently of one another, and are typically converted to supported alloys or nanoparticles after thermal treatment. [19][20][21][22][23][24][25][26][27][28][ [29][30][31][32] The purpose of this article is to compare both routes (A and B) in the case of a tantalum-iridium system. We demonstrate that, although homogeneously distributed heterometallic species are formed using both approaches, the nature of the obtained surface species, and therefore the catalytic performances of these materials, are affected by the chosen synthetic methodology.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] As a matter of course, researchers have applied this emerging technique to the 17 O nuclide, and demonstrated that 17 O SS NMR spectra could be acquired at natural abundance from nanoparticles [4,9,[12][13][15][16][17] and even from surfaces. [9,[18][19][20][21] In the majority of studies, however, the hyperpolarization of 17 O nuclei has been achieved via protons using the route e À ! 1 H!…”
mentioning
confidence: 99%